2018
DOI: 10.1016/j.ijscr.2017.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Total bilateral TMJ reconstruction for pain and dysfunction: Case report

Abstract: HighlightsThe use of TMJ protheses was configured as a good therapeutic alternative for severe conditions that do not respond to conservative treatments.A correct diagnosis of the pathology and the correct indication for reconstruction are fundamental for the success of the technique.The stock prostheses is a good alternative when there is no need for mandibular advancement and the branches are still preserved.Further studies are needed to demonstrate whether these results are long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Clinical studies published between 2005 and 2012 suggested a success rate of standard TMJ TJR ranging from 84 up to 91% [38]. Total stock or standard TMJ TJR includes a mandibular component available in three different sizes (55,50, and 45 mm) as well as a prosthetic articular fossa in different sizes (wide, medium, small), as shown in Figure 1 [21,22,32,39]. These types of prostheses have a CoCrMo alloy (ASTM type F799 or F1537) condyle coupled to the mandible ramus component composed of titanium grade V to promote the osseointegration process [37,40,41].…”
Section: Standard and Custom-made Tmj Tjr Prosthesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies published between 2005 and 2012 suggested a success rate of standard TMJ TJR ranging from 84 up to 91% [38]. Total stock or standard TMJ TJR includes a mandibular component available in three different sizes (55,50, and 45 mm) as well as a prosthetic articular fossa in different sizes (wide, medium, small), as shown in Figure 1 [21,22,32,39]. These types of prostheses have a CoCrMo alloy (ASTM type F799 or F1537) condyle coupled to the mandible ramus component composed of titanium grade V to promote the osseointegration process [37,40,41].…”
Section: Standard and Custom-made Tmj Tjr Prosthesesmentioning
confidence: 99%
“…Within the second surgery, the spacer component is removed and the selected TMJ TJR prosthesis is placed [11,21,47,48]. The benefits of standard TMJ TJR involve low cost and immediate availability [21,49,50]. Several authors report an increase in the number of standard TMJ TJR with satisfactory results of mouth opening within a period of 3 or 8 years [32,40,41,51].…”
Section: Standard and Custom-made Tmj Tjr Prosthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…et al, 2017). Suas vantagens são o baixo custo, disponibilidade imediata e preparação menos complexa para cirurgia (Lee et al, 2013;Moreira et al, 2018;Rhee et al, 2019). Vários autores relatam o aumento do número de colocações destas próteses pré-fabricadas, com resultados satisfatórios de abertura bucal dentro de um período de 3 ou 8 anos (Giannakopoulos et al, 2012;Gonzalez-Perez et al, 2020;Kanatsios et al, 2018;Westermark et al, 2011).…”
Section: A R T I G O D E R E V I S ã Ounclassified
“…As próteses personalizadas têm um comportamento superior às padronizadas devido a diversos fatores. A redução de micro-movimentos dos componentes, que põe em causa a longevidade destes dispositivos, é uma grande vantagem das próteses personalizadas, bem como o melhor posicionamento dos parafusos na fossa articular e no ramo da mandíbula, fatores que permitem maior previsibilidade dos resultados e menor tempo cirúrgico (Moreira et al, 2018). A vantagem das próteses personalizadas são a sua melhor adaptação ao leito cirúrgico (especialmente em avanços mandibulares maiores que 35mm) não sendo necessário normalmente a regularização óssea.…”
Section: Próteses Da Atm Personalizadasunclassified